CUSTOMER ENGAGEMENT AND DIGITAL BUSINESS (ROUTLEDGE, 2026)
In an age where digital disruptions rewrite the rules of commerce, Customer Engagement and Digital Business presents a timely and cutting-edge examination of how businesses must rethink engagement to thrive. This edited volume brings together a diverse group of international scholars who explore the evolving dynamics of customer engagement across a variety of technological, social, and ethical landscapes.Spanning conceptual frameworks, empirical studies, and emerging paradigms, the chapters address both the bright and dark sides of engagement in the digital age. From the emotional resonance of AI-powered brand interactions to the immersive experiences enabled by VR and Metaverse, this book probes the ways in which businesses are redefining the customer journey. Topics include actor engagement beyond the brand-consumer dyad, the strategic use of AI in product development, the impact of marketer-generated content on consumer behavior, and the ethical imperatives of service ecosystems. Equally attentive to technological advances and human values, this collection examines how gamification, AR, and generative technologies are reshaping expectations, and why meaningful engagement must be ethical, inclusive, and human-centric.Each chapter offers actionable insights for academics, practitioners, and students exploring the new frontiers of customer engagement. This book equips scholars, strategists, and digital innovators with conceptual clarity and practical foresight needed to engage meaningfully with today's empowered, tech-savvy consumers.
Keywords: Internet marketing.; Customer relations.; elektronické knihy; electronic books